PENERAPAN MODEL IMPROVE TERHADAP PENINGKATAN HASIL BELAJAR SISWA KELAS X SMA NEGERI 1 BANGKINANG KOTA PADA MATERI USAHA DAN ENERGI - Atika, Diana; Nor, M.; Yennita, Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aimed to describe the results of student learning and knowing the improvement of learning in class X SMAN 1 Bangkinang Kota with using learning models IMPROVE on work and energy. This type of research is the Pre-Experimental design with the design of the study is the comparison group intact. The subjects were students of class X SMA Negeri 1 Bangkinang Kota with academic year 2018/2019 amounted to 68 students. The research data is data that consists of learning outcomes post-test scores through the application of learning models Improv. Data were analyzed descriptively to see how improving student learning outcomes after the implementation of the learning model IMPROVE, Results of data analysis obtained by the absorption capacity of the experimental class average is higher than the average absorption control class with a score of average absorption experimental class score of 72.73 and an average absorption control class 67.45. Learning effectiveness score refers to the average absorption of each class with a score of 72.73 experimental classes including effective category and grade control 67.45 categorized quite effective. Based on the criteria of value obtained conclusion that can be drawn the conclusion that there was an increase of 9.29% learning outcomes after the implementation of the learning model Improv..Key Words : IMPROVE Model, Learning Outcomes, Work and Energy.